EXTENDING TRADITION CONCEPT OF TAHFIDZ ISLAMIC BOARDING SCHOOL DESIGN IN NGANJUK INDONESIA - Mubarok, Jalaluddin; Mutiara, Elok; Setiyowati, Ernaning (Journal of Islamic Architecture, 2018)
Â  Â Tahfidz Islamic boarding school is a traditional boarding school that focuses on learning Islam and Quran. Recently, the need for this kind of school for junior and senior high school is increasing in Indonesia. One of the cities that has a high demand for that kind of education is Nganjuk. Nganjuk has many traditional Tahfidz boarding schools that are already running for decades. The design of the existing tahfidz schools is not suitable for modern life, while people nowadays search the school in a contemporary design. There is a paradox in this statement that people want a modern design for a traditional education method. The extending tradition design approach is the appropriate answer to this problem. This study aims to find the proper design for tahfidz boarding school using extending tradition design approach. The method for this design approach used tradition as the basic idea for the design and modified it to be suitable for modern society. The concept of the design is a tradition of togetherness, the culture of continuity, and tradition of socializing. The idea is appropriate for the tahfidz and the Islamic tradition values in modern life.